INTRODUCTION OF CASE-BASED LEARNING FOR TEACHING MEDICINE IN PHASE 2ND M.B.B.S. STUDENTS - PRAVEEN KUMAR GARG; BHARAT SEJOO; PRABHU DAYAL; LAXMAN KUMAR SONI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objective of this study was to assess and compare case-based learning (CBL) with traditional teaching among phase 2 MBBS students. Methods: This study is designed as an educational interventional cross-over trial with a quantitative approach to compare two distinct clinical teaching methods at the government medical college, Pali. The primary aim is to assess the impact of CBL on the educational experiences of 2nd-year MBBS students. Results: The analysis confirms that CBL significantly improves students’ understanding and satisfaction compared to traditional teaching, offering a more effective and engaging learning experience. Conclusion: The study recommends CBL for 2nd-year medical students, as it is preferred for its engaging and effective approach to understanding and applying medical concepts.